Examining the impact of Chickering's seven principles of good practice on student attrition in online courses in the community college - Tirrell, Timothy, author; Quick, Don, advisor (Colorado State University. Libraries, 2009)
As online enrollments escalate in colleges and universities across the country, so does concern about student attrition rates in these courses, or students who drop, fail or are administratively withdrawn from the course. There is an abundance of literature addressing student success in online courses and much of this focuses on using constructivist learning theories to create learning experiences that engage the student. Also emerging from the literature is the Seven Principles of Good Instructional Practice by Checkering and Gamson as an accepted rubric for evaluating effective online instruction. This study focuses on whether the use of instructional strategies as measured by the Seven Principles of Good Practice has an effect on student attrition rates in online courses. Full and part time faculty at three community colleges in Virginia who taught at least one online course in the last three semesters completed an online survey to determine the extent they use instructional strategies reflecting the constructivist-based Seven Principles of Good Practice in their online courses. Scores from the survey were then compared to the attrition rates in their courses. Results indicated both groups strongly used instructional strategies reflecting the seven principles of good practice in their online courses and there was observed in the reported use between full and part time faculty, although full time faculty scores ranged a bit higher while part-time faculty scores tended to cluster towards the middle. When the results for the principles are examined individually rather than as a set, both groups scored weaker on principles reflecting innovative instructional strategies. However, no relation between the extent to which faculty reported using those instructional strategies and student success as measured by attrition rates could be found. Also the study results support the need for further research controlling for certain variables which are discussed in the conclusion of the study.
Keywords: attrition; Chickering, Arthur; community college; Gamson, Zelda; online; community college education; curriculum development; college students